Variation parameters for heat tolerance index of wheat - Prakash Agrawal, Ajay; Pandey, Dinesh; Pandey, Devesh (Journal of Cereal Research, 2014)
Wheat is important rabi crop in Chhattisgarh, which is grown mostlyunder irrigated condition. The late sowing and early rise in thetemperature during winter season are the major causes of the lowerproductivity. One hundred genotypes were evaluated on two dates ofsowing under late sown conditions and Heat Tolerance Index (HTI) wascalculated for seed yield and seven component characters. Most of thecharacters recorded high coefficient of variation for HTI except days tomaturity. HTI for days to flowering ranged from 0.12 (EBWYT 524) to0.76 (CG 8047). Forty three genotypes have negative index indicatinghigh grains per spike in second sowing date, moreover, genotypes Raj4187, LBPY 06-14, ESWYT 104 and CG 8040 have zero HTI and YCSN102(09), Raj 4174 have near stable grains per spike in two sowing dates.Three genotypes IBWSN 1156, EIGN 8-83 and HD 2932 (C) recordedthe zero HTI for tillers per plant. The average 1000 seed weight was33.49 percent higher in first sowing date as compare to second date.The minimum index value is 0.04 for EGPY 5, CG 8017, moreoverSBR-48, EBWYT 519 and ESWYT 528 recorded less than 0.10 index,indicating stable seed weight over different sowing dates. The seedyield per plot ranged from 260 g for IBWSN 1156 to 1100 g for CG8046 with average yield of 608.5 grams per plot first date of sowing.Under January sown conditions, mean seed yield was 357.7 gram perplot resulting in 70 percent reduction in seed yield. The seed yield perplot ranged from 180 grams for Lok 1 to 575 grams for IBWSN 1133.The HTI ranged from 0.00 (tolerance) to 0.72 (Susceptible). CG 8020,CG 8038 and LBPY 6-13 recorded the 0.00 index, but these varietiesare poor yielder than the check, hence can only be used as parentfor heat tolerance.